Profile of Food Consumption, Fe and Zn Serum at The First Trimester Pregnant Women - Yekti H Effendi; Dodik Briawan; Migi Barunawati (Media Gizi dan Keluarga, 2000)
A cross sectional study in food consumption and serum of iron and zinc in Bogor District (West Java) was conducted between August to November 1998. Interview and blood sample were collected from 60 women in the first trimester of pregnancy. Most of them were young (20 Ã‚Â¡V 30 years old), graduated from elementary school (60 %) and have low income. The staple food was rice, eaten only twice a day. Ninety percent respondent have no food taboo in their food habit. Intake of energy, protein, Vitamin C, iron, zinc and cooper were calculated from food composition value on the basis of literature. Mean daily nutrient intakes were follow ; energy 1616 kcal (73,5 % RDA), protein 52,8 (99,3 % RDA), Vitamin C 93,3 mg (347,5 % RDA), iron 23,6 mg (86,0 % RDA), zinc 7,3 mg (36,8 % RDA) and cooper 1,8 mg (122,9 % RDA). Eighty percent of pregnant women had energy intakes below the recommendation of Indonesia RDA. Mean serum iron and zinc were 90,3 Ã†â€™ÃƒÂ g/dl and 54,9 Ã†â€™ÃƒÂ g/dl. Thirty-three percent of pregnant woman were severe iron deficiency and 8,7 % zinc deficiency.